Securing multi-tenancy systems through multi DB instances and multiple databases on different physical servers - J. K. R Sastry; M. Trinath Basu (Institute of Advanced Engineering and Science, 2019)
Use of the same application by multiple users through internet as a service is supported by cloud computing system. Both the user and attacker stay in the same machine as both of them are users of the same application creating an in-secure environment. Service must ensure secrecy both at the application and data layer level. Data isolation and Application isolation are two basic aspects that must be ensured to cater for security as desired by the clients that accesses the service. In this paper a more secured mechanism has been presented that help ensuring data isolation and security when Multi-tenancy of the users to the same service has been implemented.